STUDY OF CONSUMER ACCEPTANCE ONPATIN FISH(Pangasius hypophthalmus) NUGGET WITH DIFFERENT BINDERS - Gaol, Ade Usbet Lumban; Sumarto, Sumarto; Sari, N Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study was aimedto determine the effect of different binders on patin fish nugget on consumer acceptance and the best nutritional value. The method used in this study wasa completely randomized design (CRD) with 4 treatment levels, namely N0(tapioca flour), N1(sago starch flour), N2(tapioca flour + yellow sweet potato flour), N3(sago starch flour + yellow sweet potato flour). Based on the results of thisstudy concluded that patin fish nugget with different  binders had a significant effectonthe organoleptic value (texture,  appearance, aroma), moisturecontent, ash content, fat content, and carbohydrate content.Based on the parameters tested the treatment favored by panelistsin patin fish nugget with different binderswasN3with the addition of sago starch flour and yellow sweet potato flour as many as 74 panelists (92.5%) with the characteristics of yellow sweet potato flour taste (6.76), the texture of very chewy (7.33), brownish yellow appearance (6.65), the aroma of quite yellow sweet potato flour (6.59), while the moisturecontent (47.61%), protein content (13.01%), ash content (2.03%), fat content (11.10%) and carbohydrate content (26.24%). Keywords:Pangasius hypophthalmus, Patin fish nugget, Sago starch flour, Tapioca flour, Yellowsweet potato flour